Husband Support: Supporting or Inhibiting Personal Growth Initiative of Women Leaders - Dhini Rama Dhania; Fendy Suhariadi; Fajrianthi Fajrianthi; Suryanto Suryanto (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
Various programs were developed by the company to improve the capacity of women leaders. However, on the other hand, the factor of family support, especially the husband support, has so far been neglected in scientific research related to women leaders. Therefore, this study aimed to understand the role of husband support in the personal growth of women leaders. This study used a phenomenological qualitative approach, using semi-structured interviews with 6 women leaders. The results show that what motivates women leaders in their personal growth initiative is wanting to get out of their comfort zone, being challenged to become useful people, and having a clear career path. Besides, forms of support such as not complaining a lot, providing real assistance, providing solutions or information, providing emotional support, and giving space for the women to be alone or free to do things are forms of support needed by women leaders in Indonesia. Moreover, jealous husbands and husbands who forbid and demand many things are felt to inhibit the personal growth initiative of women leaders. Furthermore, the husband's dominant role so far is to support the personal growth initiative process.